Heritage Tourism and Vibrant Life of the Baan Lao Community, Chao Phraya River, Bangkok, Thailand - Choomgrant, Korakit; Sukharomana, Renu (Journal of Reviews on Global Economics, 2017)
The reputations of primary and secondary tourist destinations are hierarchically created through its value to the nation. Prioritizing a conservation project and tourism development can have major differences. Values attached to a destination by inhabitants are different from those of tourists, and are often influenced by the promotional campaigns designed by authorized agencies. A primary destination is then worthy of promotion and conservation as it serves a nation's purposes economically, socially and politically, while a destination that is not corresponding in such ways is usually disregarded. Koh Kret is an established primary tourism destination for domestic visitors, though not for international visitors. However, the Baan Lao Community can be developed as a secondary tourism destination for visitors to Koh Kret. Koh Kret and Baan Lao Community in Thailand are illustrations of significance and value. By understanding the Baan Lao community's significance, value and values, it is an opportunity to develop the area as a secondary tourist destination, and help preserve the way of life of local inhabitants along the Chao Phraya River in Bangkok, Thailand.